2013
DOI: 10.4067/s0717-95022013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Sella Turcica Bridge and Clinoid Enlargement in Lateral Cephalometric Plain Film Radiography from Peruvians

Abstract: 0.05) between sella turcica bridge and clinoid enlargement with respect to sex, and age groups (under 18 and over 18). The sella turcica bridge and clinoid enlargement are not so infrequent findings in the population studied, our results are similar to those reported in the literature. The existence of a sella turcica bridge or a clinoid enlargement must be considered as a structural anomaly that may influence the prognosis of surgical procedures of the sella turcica.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…They are used to evaluate the craniofacial and dental structures, but they also include other diagnostics information about the skull, face and upper cervical spine, and various occult pathologies and rare normal variants involving the head or spine (Pérez et al, 2013). Identifying the affected side of atlas is very difficult with lateral radiographic views because the presentation of PP can be uni or bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…They are used to evaluate the craniofacial and dental structures, but they also include other diagnostics information about the skull, face and upper cervical spine, and various occult pathologies and rare normal variants involving the head or spine (Pérez et al, 2013). Identifying the affected side of atlas is very difficult with lateral radiographic views because the presentation of PP can be uni or bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for determining the PP, STB and CLEN were the same utilized in previous publications (Pérez et al, 2013(Pérez et al, , 2014: with the samples of the studies of PP, STB and CLEN realized in non-cleft Peruvian patients.…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of Ponticulus Posticus (complete and partial) in the Atlas vertebrae; the Sella Turcica Bridge and the Clinoid Enlargement in Peruvians were determined in two distinct studies (Pérez et al, 2013(Pérez et al, , 2014; those frequencies and the samples where they come from could be utilized as control groups that can be matched with other samples of patients with specific conditions such as Cleft lip and palate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological variations of sella turcica were reported in cases with severe craniofacial deviation, genetic abnormalities, syndrome abnormalities as well as dental anomalies. Many researchers report that the prevalence of morphology of sella turcica such as the presence of bridging is more common in subjects with dental anomalies, cleft lip and palate and other anomalious variations [9,12]. Jones et al 2005, found that the incidence of bridging on healthy subjects ranged from 3.8 to 13% [8].…”
mentioning
confidence: 99%